Correlation Between Immune Lymphoid Cells and Plasmacytoid Dendritic Cells in Human Colon Cancer - Wu, Jing; Cheng, Hang; Wang, Helei; Zang, Guoxia; Qi, Lingli; Lv, Xinping; Liu, Chunyan; Zhu, Shan; Zhang, Mingyou; Cui, Jiuwei; Ueno, Hideki; Liu, Yong-Jun; et al. (Frontiers in Immunology, 2021)
Background: Innate lymphoid cells (ILCs), so far studied mostly in mouse models, are important tissue-resident innate immune cells that play important roles in the colorectal cancer microenvironment and maintain the mucosal tissue homeostasis. Plasmacytoid dendritic cells (pDCs) present complexity in various tumor types and are correlated with poor prognosis. pDCs can promote HIV-1–induced group 3 ILC (ILC3) depletion through the CD95 pathway. However, the role of ILC3s in human colon cancer and their correlation with other immune cells, especially pDCs, remain unclear. Methods: We characterised ILCs and pDCs in the tumor microenvironment of 58 colon cancer patients by flow cytometry and selected three patients for RNA sequencing. Results: ILC3s were negatively correlated, and pDCs were positively correlated, with cancer pathological grade. There was a negative correlation between the numbers of ILC3s and pDCs in tumor tissues. RNA sequencing confirmed the correlations between ILC3s and pDCs and highlighted the potential function of many ILC- and pDC-associated differentially expressed genes in the regulation of tumor immunity. pDCs can induce apoptosis of ILC3s through the CD95 pathway in the tumor microenvironment. Conclusions: One of the interactions between ILC3s and pDCs is via the CD95 pathway, which may help explain the role of ILC3s in colon cancer.